Linguistic and didactic challenges of academic writing - García Ruiz, María Aurora; Salazar García, Ventura (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This paper critically reviews some of the current research lines on academic writing. From a linguistic perspective, academic writing constitutes a specific mode of the scientific register of a given language. Such a register functions as a social and discourse practice only within a semiotic setting to which we give the name of scientosphere. From a pedagogic point of view, academic writing is an operative knowledge that can be gradually acquired through adequate academic literacy. In this field, didactic intervention currently faces various challenges, such as coordination between pre-university and university education, the emergence of new training needs derived from changes in the university curriculum and, above all, the communicative horizon opened by the digital revolution. Within this framework, we describe an academic literacy experience developed at the University of Jaén